Serological prevalence of the Schmallenberg virus in domestic and wild hosts worldwide: a systematic review and meta-analysis - Dagnaw, Melkie; Solomon, Atsede; Dagnew, Binyam (Frontiers in Veterinary Science, 2024)
Schmallenberg virus (SBV) is an arthropod-borne virus that emerged recently in northwestern Europe in 2011 that affects domestic and wild ruminants and induces abortion, stillbirth, and newborns with congenital anomalies. Since its discovery, SBV has spread very rapidly to too many countries in the world. The overall serological investigation of SBV is needed to improve modeling predictions and assess the overall impact on ruminant animals, which helps to design interventions for control and prevention strategies. Thus, this study aimed to estimate the overall serological assay of SBV in both domestic and wild ruminants around the world. This systematic review was conducted as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. International databases were employed To search for relevant articles. The pooled prevalence with a 95% confidence interval was calculated with a random effects model. The Cochran’s Q test, τ2, and I2 were used to assess the sources of heterogeneity. In the current meta-analysis, a total of 41 articles were included. The overall pooled proportion of SBV in domestic and wild ruminants was 49 and 26%, respectively. Substantial heterogeneity was observed in studies on domestic ruminants (I2 = 99.7%; p < 0.01) and studies on wild ruminants (I2 = 97.9%; p < 0.01). The pooled prevalence of SBV was significantly associated with publication time, detection techniques, and species of animals. According to the subgroup analysis, the highest pooled prevalence of SBV was reported in cattle (59%), followed by sheep (37%) and goat (18%). In addition to the subgroup analysis based on publication year, the pooled prevalence of SBV infection has become endemic since 2013 (49%) among domestic animals in the world. Of the diagnostic tests used, the highest anti-SBV antibodies (66%) were detected by a virus neutralization test. In this meta-analysis, the major wild animals that were infected by SBV were red deer, roe deer, fallow deer, mouflon, and wild boar. The highest sub-pooled prevalence of SBV was found in roe deer (46%), followed by fallow deer (30%), red deer (27%), mouflon (22%), and wild boar (11%). In general, the prevalence of SBV was high in cattle among domestic ruminants and in roe deer among wild animals. According to the current information provided by this meta-analysis, evidence-based risk management measures should be established to restrict SBV spread in both domestic and wild ruminants.